1994
DOI: 10.1111/j.1399-302x.1994.tb00067.x
|View full text |Cite
|
Sign up to set email alerts
|

The tet(Q) gene in bacteria isolated from patients with refractory periodontal disease

Abstract: Twenty-two tetracycline-resistant (tetr) anaerobic and facultative anaerobic bacteria isolated from periodontal pockets of 12 patients with refractory periodontitis were examined for the presence of the Tet Q determinant by DNA-DNA hybridization. Dot blots of bacterial DNA were tested with an intragenic digoxigenin-labelled tet(Q) probe consisting of a 1.45 kb EcoRI/PvuII fragment from plasmid pNFD13-2. Southern blots of chromosomal DNA digested with the restriction enzyme EcoRI were also examined. The tet(Q) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 21 publications
3
26
0
Order By: Relevance
“…Tet(Q) was mainly found in gram-negative organisms (Table 3). Tet(Q) has been reported to be common in gramnegative oral bacteria that are associated with periodontal destruction (13,24). However, this study has shown for the first time that tet(Q) is present in commensal Neisseria spp.…”
Section: Resultsmentioning
confidence: 45%
See 1 more Smart Citation
“…Tet(Q) was mainly found in gram-negative organisms (Table 3). Tet(Q) has been reported to be common in gramnegative oral bacteria that are associated with periodontal destruction (13,24). However, this study has shown for the first time that tet(Q) is present in commensal Neisseria spp.…”
Section: Resultsmentioning
confidence: 45%
“…tet(M) has been found in many different bacterial genera in the oral cavity (12); tet(O) and tet(Q) have been isolated from gram-positive and gram-negative oral species, respectively (21,24,25); tet(K) and tet(L) have been isolated from Streptomyces species (26); and several efflux genes have been isolated from gram-negative oral species (32). However, the prevalence of the newly discovered tetracycline resistance genes in the oral cavity has not been investigated.…”
Section: Tet(d) Tet(e) Tet(g) Tet(h) Tet(j) Tet(y) Tet(z) Tet(mentioning
confidence: 99%
“…This gene is now found in a number of Prevotella spp. from the oral cavity as well as in other Gram-negative oral genera such as Mitsuokella, Capnocytophaga, and Veillonella [101]. A total of six different Gram-negative genera currently have been shown to carry this gene (Table 1).…”
Section: Gram-negative Bacteriamentioning
confidence: 99%
“…This gene is now found in a number of Prevotella spp. from the oral cavity and in other oral gramnegative genera such as Capnocytophaga, Mitsuokella, Selenomonas, and Veillonella (200,201,230). From other sites we found tet(Q) in gram-positive Clostridium, Gardnerella, and Peptostreptococcus spp.…”
Section: Tet(a) Tet(b) Tet(c) Tet(d) Tet(e) Tet(g) Tet(h) Tet(mentioning
confidence: 99%